Which factors influence the oral health of nursing-home residents with cognitive and motor impairments? - Klotz, Anna-Luisa; Zajac, Melania; Ehret, Judith; Kilian, Samuel; Rammelsberg, Peter; Zenthöfer, Andreas (Aging clinical and experimental research, 2021)
There is limited information available about the oral and denture hygiene and oral health of nursing-home residents with cognitive and motor impairments.